Development of engineering and innovation skills - Nagyné Kondor, Rita; Sipos, Dóra (International Journal of Engineering and Management Sciences, 2020)
Spatial visualization skills have an important role in teaching and learning of engineering studies. Many studies have shown that there are correlations between various measures of spatial skills and performance in particular Science, Technology, Engineering and Mathematics (STEM). Many engineering students have problems with solving mathematics problems, using mathematical models in practice, imagining a spatial figure and therefore to solve the spatial geometry exercises, so development of these abilities is very important. We have developed special tools and worksheets for development of engineering and innovation skills.